Motivation for smoking cessation among drug-using smokers under methadone maintenance treatment in Vietnam. Issue 1 (December 2015) - Tran, Bach; Nguyen, Long; Do, Huyen; Nguyen, Nhung; Phan, Huong; Dunne, Michael; Latkin, Carl
Abstract Background Smoking cessation treatment service is concerned to be a critical element in methadone maintenance treatment (MMT) in order to diminish the effect of smoke on health outcomes. To implement the smoking cessation services in Vietnam, we examined the stages of change to quit and determined associated factors among MMT patients. Methods We conducted a cross-sectional survey with 1016 MMT patients in five clinics in Hanoi and Nam Dinh province, of those, 932 (91.7 %) were ever-smokers. Patients were classified into four groups: "pre-contemplation, " "contemplation, " "preparation, " and "action and maintenance" by using the transtheoretical model. Multivariate logistic regression was applied to determine the associated factor for intention and action to quit smoking. Results Overall, 96 % were not actively trying to quit or maintain abstinence. Age older than 45, HIV-positive status, and residence in Hanoi were negatively associated with intention to quit. Meanwhile, higher levels of nicotine dependence and number of years of smoking negatively associated with quitting and abstinence. Conclusions The study indicated the high rate of MMT smokers being in pre-contemplation stage but low proportion of quitting and maintaining abstinence. It emphasizes the importance of availability and accessibility of information about smoking cessation therapies and services. Integrating cessation programs into health-care services should be considered to provide tailored interventions for different patient groups.